2007
DOI: 10.2527/jas.2006-631
|View full text |Cite
|
Sign up to set email alerts
|

Selection for litter size at day five to improve litter size at weaning and piglet survival rate1

Abstract: Selection for total number of piglets born (TNB) since 1992 has led to a significant increase in this trait in Danish Landrace and Danish Yorkshire but has also been accompanied by an increase in piglet mortality. The objective of this study was to estimate the genetic and phenotypic parameters for litter size and survival to find alternative selection criteria to improve litter size at weaning. Data from Landrace (9,300 litters) and Yorkshire (6,861 litters) were analyzed using REML based on a linear model in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
128
4
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(165 citation statements)
references
References 16 publications
22
128
4
11
Order By: Relevance
“…Further, the estimates of genetic correlations for survival between different periods were low or moderate, and most were not significantly different from zero. The results agree with those of previous studies based on litter records Su et al, 2007) or on piglet records (Arango et al, 2006). Serenius et al (2004) obtained an estimate of the genetic correlation between the proportion of stillbirth and piglet mortality from birth to weaning close to zero.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Further, the estimates of genetic correlations for survival between different periods were low or moderate, and most were not significantly different from zero. The results agree with those of previous studies based on litter records Su et al, 2007) or on piglet records (Arango et al, 2006). Serenius et al (2004) obtained an estimate of the genetic correlation between the proportion of stillbirth and piglet mortality from birth to weaning close to zero.…”
Section: Discussionsupporting
confidence: 91%
“…Arango et al (2005) reported estimates of heritability for number of piglets born dead of 0.09, 0.10 and 0.11 in parity 1, 2 and 3, respectively. Su et al (2007) reported estimates of heritabilities for survival rate at farrowing and during early suckling ranging from 0.042 to 0.129, and near to zero for survival rate during late suckling period, based on sow genetic component at the litter level. Several studies have included the direct additive genetic effect of the piglet in the analysis on piglet survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2). Irgang et al (1994) Por fim, por meio da correlação de Spearman (correlação de posto) entre os valores genéticos do NLNV e NLV5, período que considera a capacidade de criação da fêmea, e menor mortalidade dos leitões (Su et al, 2007), foram obtidos valores, tanto para o primeiro parto quanto para o segundo, próximos da unidade (0,99), sugerindo que o registro do NLV5 poderia ser dispensado.…”
Section: Resultsunclassified